Understanding Radicalization - Yanuar Rizal (Sekolah Tinggi Ilmu Kepolisian, 2018)
This essay is a critical view of the concept of radicalization proposed by Clark McCauley and Sophia Moskalenko who explained the mechanism of political radicalization as one of the many models to describe the role of radicalization in the context of terrorism. Analytically, it is necessary to distinguish between radicalization that does not include violent behavior as existing in political expression in democratic societies and radicalization that defines violent behavior as existing in the characteristics of terrorist groups. In this way it will enable us to understand appropriate counterterrorism policies.